Pharmacological cholinergic stimulation as a therapeutic tool in experimental necrotizing pancreatitis - Schneider, Lutz; Jabrailova, Bahar; Soliman, Hussein; Hofer, Stefan; Strobel, Oliver; Hackert, Thilo; Büchler, Markus W.; Werner, Jens (Pancreas, 2014)
Objectives - The endogenous immune response is influenced by the stimulation of the vagal nerve. Stimulation or ablation has a direct impact on the release of pro- and anti-inflammatory mediators. In the progression of acute pancreatitis from local to systemic disease, these mediators play a pivotal role. This study evaluates the effect of pharmacologic stimulation of the cholinergic system on pancreatic damage in experimental necrotizing pancreatitis. - Methods - Experimental severe necrotizing pancreatitis was induced in male Wistar rats using the glycodeoxycholic acid model. Animals with acute pancreatitis (n = 6) were compared with animals with acute pancreatitis and prophylactic or therapeutic pharmacologic activation of the cholinergic system using nicotine, physostigmine, or neostigmine (n = 36). Twelve hours after the induction of acute pancreatitis, morphological damage as well as the myeloperoxidase levels of the pancreas and the serum levels of high-mobility group box 1 protein were evaluated. - Results - Prophylactic and delayed therapeutic application of nicotine, physostigmine, or neostigmine significantly attenuated the severity of acute pancreatitis 12 hours after the induction of severe necrotizing pancreatitis compared with untreated controls as evaluated with histological scores, myeloperoxidase, and high-mobility group box 1 levels (P < 0.05). Conclusions - Stimulation of the cholinergic system is useful to attenuate damage in experimental acute pancreatitis. Not only prophylactic but also delayed application was effective in the present study.